HUBUNGAN KEADILAN ORGANISASI, PERSEPSI DUKUNGAN ORGANISASI DENGAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) GURU DI JAKARTA TIMUR, INDONESIA - Supadi Supadi; Bedjo Sujanto; Evitha Soraya (Program Studi Manajemen Pendidikan, 2018)
ABSTRACT This study aims to obtain real information of the relationship between Organizational justice and Organizational Citizenship Behavior (OCB), the relationship between the Perceived Organizational Support (POS) and Organizational Citizenship Behavior, the relationship between the combined organizational justice and the perceived organizational support (POS) on the Organizational Citizenship Behavior (OCB) The method used in this research is a survey with correlational techniques using instrument in data collection. The study was conducted at state senior high schools in East Jakarta, 2017. The total of population was 2156, with 96 samples selected by performing Slovin’s formula. The results showed that the organizational justice has positive relationship with Organizational Citizenship Behavior (OCB). Also, the perceived organizational support is positively related with organizational citizenship behavior. At last, the combined organizational justice and the perceived organizational support have positive relationship with the organizational citizenship behavior.